Pola makan, penyakit infeksi, dan status gizi anak balita pengungsi di Kabupaten Pidie Provinsi Nanggroe Aceh Darussalam - Irwansyah Putra; Endy Paryanto Prawirohartono; Madarina Julia (Jurnal Gizi Klinik Indonesia, 2007)
Background: The declaration of Martial Law in Aceh Province have been held, they evacuate themselves to save from the risks when bombardment happen. In refugee camp, there were problems, like improperly place to live, lack of food, and lack of water. This condition will make the nutritional and health status become worse. It can be signed by the increasing of under nutrition prevalence.Objective: The objective of this study was to determine the food consumption pattern, breastfeeding pattern, nutritional intake, infection diseases, and nutritional status of infant under five years old in refugee camp.Method: This was an observational study with cross sectional design. This study was conducted in Keunire refugee camp, Pidie District, Nanggroe Aceh Darussalam Province. Subjects of this study were infants under five years old. Data were collected by interview using open questionnaire, while nutritional intake data were collected by recall method and analyzed using computer. The assesment of nutritional intake was using anthropometry method. Data were analyzed using chi square test and t-test.Results: General and specific feeding pattern were given by the team of disaster and refugee tackling of Pidie District for Keunire refugee camp. Specific feeding pattern was given to the infant of under five years old as a food supplement. That food supplement should fulfill 15.4-30.5% energy and 28.5% - 69.1% protein requirements. Breastfeeding pattern changed into more regular when they were ini refugee camp, because their children were thirsty and crying. Mean of energy and protein intake of refugee infant of under five years old were higher than that of non refugee. The under nutrition prevalences of refugee infant of under five years old were 21.7% (WHZ), 32.5% (WAZ), while that prevalences of non refugee infant were 23.8% (WHZ) and 39.7% (WAZ). Statistically, there were no differences in under nutrition prevalences between both of them. Nutritional status had association with energy intake, protein intake, and infection diseas in refugee camp.Conclusions: There was changing in breastfeeding pattern in refugee camp. There were also differences in mean of energy and protein intake between refugee and non refugee infant of under five years old, but there was no difference in nutritional status.